2016
DOI: 10.1021/acs.jpcb.6b02517
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trehalose for the Stabilization of Proteins

Abstract: Understanding of how the stabilization mechanism of trehalose operates on biological molecules against different types of environmental stress could prove to gain great advancements in many different types of conservation techniques, such as cryopreservation or freeze-drying. Many theories exist that aim to explain why trehalose possesses an extraordinary ability to stabilize biomolecules. However, all of them just explain parts of its mechanism and a comprehensive picture is still lacking. In this study, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 32 publications
8
103
0
Order By: Relevance
“…Our experiment also revealed that vitrification in the absence of trehalose (0.0 M) impairs developmental competence in vitri- (Bosch et al, 2016) and stabilizing the structural and functional integrity of cell membrane in lowwater media (Kaushik & Bhat, 2003;Olsson, Jansson, & Swenson, 2016…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our experiment also revealed that vitrification in the absence of trehalose (0.0 M) impairs developmental competence in vitri- (Bosch et al, 2016) and stabilizing the structural and functional integrity of cell membrane in lowwater media (Kaushik & Bhat, 2003;Olsson, Jansson, & Swenson, 2016…”
Section: Discussionsupporting
confidence: 53%
“…Our findings suggest that the detrimental effects of CPAs on ZP were remarkably reduced in the presence of trehalose. Trehalose has been recently found to be useful in preventing the cryodamage (Bosch et al, ) and stabilizing the structural and functional integrity of cell membrane in low‐water media (Kaushik & Bhat, ; Olsson, Jansson, & Swenson, ) . The results of several studies show that stabilizing effects of sugars in general and trehalose in particular, are related to a specific interaction of sugars with biological molecules in bilayer membranes (Jain & Roy, ; Konov et al, ; Olsson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[137] Althoughb oth thermodynamic models are commonly used to explain and predict the influence of cosolvents on the folding equilibrium of biomolecules, it mayn ot only be the (un)favorable interactions, but also as tructuralo re nergetic change of the hydration shell which favors or disfavors the solvation of hydrophobic and hydrophilic moieties of biomolecules. [138][139][140][141] Furthermore,i tm ust be taken into account that the addition of high concentrations of cosolventc an induce a significant decrease of the water activity and thus generate an osmotics tress that may suck water molecules out from the internal cavities andh ydration shell of the biomolecule. Depending on whether water is released or incorporated upon unfolding, the folding equilibrium will be changed accordingly.…”
Section: Transfer Modelmentioning
confidence: 99%
“…Tre has been recognized as an exceptional protein stabilizer [8,28,29], and this property of Tre is considered crucial to protect cells from stress. A number of studies have been performed to decipher the mechanism of action of Tre [30][31][32].…”
Section: Discussionmentioning
confidence: 99%